The Reality of Faculty Training at Jordanian Universities in the Governorates of Irbid and Ajlun - AbuAlkishik , Mohammad Nayef Okleh (Dirasat: Educational Sciences, 2020)
This study aims at investigating the reality of training of faculty of Jordanian universities in the governorates of Irbid and Ajlun and its relationship to some variables; university type (public or private), faculty gender, and position (instructor, department’s head, dean). The study followed a descriptive correlation methodology, and consisted a sample of (381) individuals who were randomly selected during second term 2017/2018. The researcher used a developed questionnaire that consisted of (46) items, after ensuring the appropraiteness of its psychometric means for usage. The findings revealed that the reality of faculty training was of a moderate level. It also revealed that no differences in the level of training according to variables of university type, position or gender occurred . The findings further indicated a positive correlation between the degree of faculty training and their performance. The researcher recommends to increase training opportunities for faculty in Jordanian universities in areas of instructional strategies, training on using technology in teaching and test development.